The effect of cyclooxygenase-2 inhibition on pentylenetetrazole-induced seizure threshold in mice - Azam Mesdaghinia; Paria Khazaee; Azhdar Heydari (Fiyz̤, 2018)
Background: Previous studies have shown the protective effect of cyclooxygenase (COX) enzyme in development of convulsions. However, involvement of COX-2 in the pathogenesis of epilepsy is not yet well-known. The present study was designed to investigate the effect of celecoxib and nimesulide (selective COX-2 inhibitors) on pentylenetetrazole (PTZ)-induced clonic seizure threshold in mice. Materials and Methods: In this study, white male mice were randomly divided into 13 groups including control groups, solvent (Tween 80) and eleven experimental groups which received celecoxib (2.5, 5 and 10 mg/kg), nimesulide (2.5, 5 and 10 mg/kg), diazepam (0.1, 0.5 and 5 mg/kg), and combination of non-effective dose of diazepam with celecoxib or nimesulide. Pentylenetetrazol-induced clonic seizure threshold was assessed in all groups. Results: Nimesulide (2.5 and 5 mg/kg), celecoxib (2.5 and 5 mg/kg), and diazepam (0.5 and 5 mg/kg) significantly increased the PTZ-induced seizure threshold compared with the solvent group (P<0.05). Also, only combination of sub-effective dose of diazepam (0.1 mg/kg) with celecoxib (2.5 mg/kg) showed a significant protective effect against PTZ-induced seizure threshold (P<0.01). Conclusion: Findings of the current study show the possible role of COX-2 isoenzyme in the pathophysiology of epilepsy. It is possible that some COX-2 inhibitors such as celecoxib act through GABAergic neurons and reduce excitability by increasing GABA release. Also, the difference between the effects of celecoxib and nimesulide can be attributed to the effect of these two compounds on COX-1 and COX-2 expression.